PENENTUAN RUTE TERBAIK PADA WSN (WIRELESS SENSOR NETWORK) BERDASARKAN PARAMETER RSSI (RECEIVED SIGNAL STRENGTH INDICATOR) - Aderusman, Rizky; Jusak, Jusak; Triwidyastuti, Yosefine (Journal of Control and Network Systems (JCONES), 2016)
Wireless sensor network (WSN) is a wireless network consisting of a collection of nodes that are scattered in a particular area. Each node has the ability to collect data and communicate with other nodes. However many studies showed that the WSN technology bears some drawbacks. One of the weakness is in terms of efficiency of energy utilization. Ineffectiveness of energy utilization in the WSN mainly caused by long and complex algorithms for route/path determination.In this work determination of the best route is implemented by comparing parameters, like RSSI (Received Signal Strength Indicator) for the selection of the route, by adapting mechanism in routing protocol OSPF (Open Shortest Path First). For testing the routing protocol, we used temperature data acquired from LM35 sensors. Sensors are planned and then implemented on all nodes WSN. By implementing these schemes for routing determination, the WSN is able to produce better quality of data and minimum energy usage measured for WSN with a distance of sending and receiving data between 1-40 meters for indoor setup. For outdoors environment, the study showed that the system has a range of up to 1-100 meters only. It is evident from the study, that the route is able to be established well (27 success out of 30 trials).